Aspergillosis in peacocks - Case Report - Edina Sesztáková; Vladimír Vrabec; Katarína Kuzyšinová; Ladislav Molnár; Zuzana Ševčíková; Eva Čonková (International Journal of Veterinary Science and Research - Peertechz Publications, 2022)
The work describes two cases of Indian peacocks (Pavo cristatus) originating from extensive breeding, in which pulmonary aspergillosis and aerosacculitis were diagnosed. A clinical examination revealed difficult breathing with an open beak, gradual apathy, decreased appetite, and weight loss in both affected individuals. During the endoscopic examination, a yellow, caseous mass was diagnosed in the area of ​​the margo caudalis of the lung. Pathological autopsy in both cases revealed a granuloma in the area of ​​the left lung parenchyma and aerosacculitis. Fungal hyphae were detected in the granulomas by pathological-histological examination, and Aspergillus fumigatus and Aspergillus parasiticus were diagnosed by mycological culture.